COMPARATIVE ANTIBACTERIAL ACTIVITY OF FRUITING BODY EXTRACTS FROM PLEUROTUS OSTREATUS GROWN ON SUBSTRATES SUPPLEMENTED WITH CAROXYLON CYCLOPHYLLA AND ATRIPLEX TATARICA AGAINST PATHOGENIC BACTERIA AND COMMON ANTIBIOTICS - A. Sh. A. Lafi; I. A. Abed; N. T. Hamdan; J. S. Alkobaisy; H. H. Mutlaq (مجلة الأنبار للعلوم الزراعية)
This study investigated the effect of the active compounds in Pleurotus ostreatus fruiting body extracts on substrates enriched by two desert weeds containing 10% Caroxylon cyclophyllum and Atriplex tatarica and 2% urea as a control. Two extraction methods using ethanol and methanol were done for three treatments and applied as antibiotics against three pathogenic bacteria (Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli). Results showed that the ethanolic extract of the urea-supplemented substrate fruiting bodies produced the best inhibition zones at 18mm against P. aeruginosa and 16mm against E. coli, and a low inhibition rate of 10mm for S. aureus. Also, the ethanolic extract of the fruiting bodies of the Caroxylon cyclophylla-supplemented substrate recorded a higher inhibition diameter of 17mm against S. aureus and a lower area of 12mm against P. aeruginosa. In contrast, the inhibitory effect decreased with the ethanolic extract of fruiting bodies of the Atriplex tatarica-supplemented substrate at 10-14mm for both P. aeruginosa and E. coli. However, the methanolic extract of fruiting bodies of the urea-supplemented substrate showed apparent inhibition (10-16mm) against all bacteria. The methanolic extract of fruiting bodies produced substrates enriched by Atriplex tatarica, and Caroxylon cyclophyllum showed inhibitory effects ranging between 13-14mm and 10-12 mm, respectively. The reason for the inhibitory effect is related to the identified active compounds in these extracts, especially Caroxylon cyclophyllum. As such, these extracts can be used as drugs to eliminate these bacteria isolates